Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-18 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
A. Improvement of high-load coordination dynamics (CD) values in a patient with severe brain injury upon coordination dynamics therapy for several years. The high-load CD values were obtained by summing up the single CD values for forward and backward exercising, ∆ (high-load CD value) = ∆20N + ∆50N + 100N + ∆150N + 200N + ∆150N + ∆100N + ∆100N + ∆50N + ∆20N + ∆20N). B, C. For comparing the rate of repair, the improvement curves of the high-load coordination dynamics values of an athlete (C) and a healthy pupil (B) are inserted. Note that the brain-injured patient needed much more time to achieve similar good CD values. D. Continuation of therapy. The substantial improvement of the high-load CD values (lower values), in the middle of 2018, motivated the patient Sotiris to continue his therapy at the limit.